For the following system, use the second equation to make a substitution for y in the first equation.

2x + y = 6
y = 3x + 4

What is the resulting equation?

y + 2x + y = 6
2x + y + 3x + 4 = 6
2x + (3x + 4) = 6

Respuesta :

CPED

Answer:

Option C: 2x + (3x + 4) = 6

Step-by-step explanation:

Given that:

2x + y = 6  ------------- eq1

y = 3x + 4 ------------- eq2

By putting value of y from eq2 in eq1 we get:

2x + (3x + 4) = 6

I hope it will help you!

Answer:

For the following system, use the second equation to make a substitution for y in the first equation.  

2x + y = 6

y = 3x + 4

substitute y = 3x + 4 into 2x + y = 6

2x + y = 6

2x +( 3x + 4) = 6

answer is 2x + (3x + 4) = 6 (last choice(

Step-by-step explanation:

ACCESS MORE